Implementing Innovative Mechanisms for Enhancing the Quality of Forensic Services via New Forensic Legislation - G. G. Omelyanyuk (Теория и практика судебной экспертизы, 2014)
The paper lays out the prospects for implementing mechanisms of forensic methodologyvalidation, pro!ciency certi!cation of forensic experts, and certi!cation of methodologyframeworks to support forensic operations, and substantiates the need to include these mechanisms in the proposed federal law «On forensic operations in the Russian Federation».